Validation of KASP assays associated with barley adaptation and productivity traits - Genievskaya, Yu.; Almerekova, Sh.; Chudinov, V.; Turuspekov, Ye.; Abugalieva, S. (Eurasian Journal of Applied Biotechnology, 2022)
Barley (Hordeum vulgare L.) is an important cereal crop traditionally used in animal feed, malting, and food production. In Kazakhstan, barley is the second most cultivated cereal grain. However, despite the long history of barley cultivation in Kazakhstan, traditional breeding methods prevail here. The introduction of marker-assisted selection (MAS) in the breeding process may improve the adaptation and productivity of local cultivars, as well as help in the development of new ones. For that, validation of 23 kompetitive allele-specific PCR (KASP) assays for adaptation and productivity traits developed using previous GWAS results was performed. The collection of 35 two-rowed barley promising lines was grown at the Kazakh research institute of agriculture and plant growing (KRIAPG, Almaty region, Kazakhstan) in 2021 and studied for 5 adaptation-related (heading time, heading-maturity time, plant height, peduncle length, and spike length) and 5 productivity-related (number of kernels per spike, the weight of kernels per spike, weight of kernels per plant, thousand kernels weight, and yield per m2) traits. The same collection was genotyped using 23 KASP assays. As a result, 21 KASPs demonstrated a good level of polymorphism (MAF > 0.10 and I > 0.36) in the studied barley collection. Six KASP assays confirmed their associations with adaptation and productivity traits (P < 0.05); nine KASPs were associated with other agronomic traits (P < 0.05). Nine KASP assays were identified for adaptation traits, one assay was detected for productivity traits and six KASPs were found to be associated with both types of traits. Four KASP assays (ipbb_hv_9, ipbb_hv_101, ipbb_hv_109, and ipbb_hv_110) confirmed significant (P < 0.05) effect of shorter heading-maturity time on higher productivity traits under stress conditions of south-east Kazakhstan. Thus, in this study fifteen out of the studied twenty-one KASP assays were validated for their associations with adaptation and productivity traits and potentially can be included in the barley breeding projects.